(untitled) (KULT_online, 2017)
Who is paying for our lifestyle? With these volumes on “externalization society” and “imperial mode of living” we are confronted with multi-layered crises such as climate change, growing global inequalities, and the exhaustion of natural resources. In light of these pressing societal issues, it is no coincidence that two books were published recently that broach the issue of the crisis of our global development model and our way of living. While the sociologist Stephan Lessenich (Munich) coined the term “Externalisierungsgesellschaft” in his book from 2016, the two political scientists Ulrich Brand (Vienna) and Markus Wissen (Berlin) submitted an analysis of the “imperial Lebensweise” in 2017. Both books demonstrate impressively that our consumer society has its price, one which is paid first and foremost by the people in the global South.